1997
DOI: 10.1177/026835559701200405
|View full text |Cite
|
Sign up to set email alerts
|

Graduated Compression Treatment in Patients with Chronic Venous Insufficiency: A Study Comparing Low and Medium Grade Compression Stockings

Abstract: Objective. Patients with chronic venous insufficiency (CVI) benefit subjectively from treatment with graduated compression stockings. Usually, class II compression is used in patients with CVl grade n. The present study investigates possible differences between graduated compression of classes I and II. Design. Randomized study. Setting. Department of Vascular Surgery and Vascular Laboratory, University Hospital, Lund. Patients and Methods. Thirty-one patients, nine male and 22 female (59 legs), all with grade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 4 publications
(3 reference statements)
0
20
0
Order By: Relevance
“…17 Some studies reported that low-compression stockings were as effective as high-compression stockings but had a better compliance rate. 16,18 A meta-analysis of 11 RCTs reported that compression of 15-20 mm Hg showed beneficial effects on edema and symptoms, as compared with compression of less than 10 mm Hg or no compression; there was no difference between compression of 10-20 mm Hg and greater than 20 mm Hg. 19 There was insufficient evidence to determine which length of graduated compression stocking (below knee or thigh length) was most beneficial.…”
Section: Uncomplicated Varicose Veinsmentioning
confidence: 99%
“…17 Some studies reported that low-compression stockings were as effective as high-compression stockings but had a better compliance rate. 16,18 A meta-analysis of 11 RCTs reported that compression of 15-20 mm Hg showed beneficial effects on edema and symptoms, as compared with compression of less than 10 mm Hg or no compression; there was no difference between compression of 10-20 mm Hg and greater than 20 mm Hg. 19 There was insufficient evidence to determine which length of graduated compression stocking (below knee or thigh length) was most beneficial.…”
Section: Uncomplicated Varicose Veinsmentioning
confidence: 99%
“…The studies were published between 1997 and 2013 and included a total of 684 participants with chronic venous insufficiency. Two studies were from Australia [20,21], one from England [22], one from Ireland [23] and one from Sweden [24].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore class I compression may be recommended over class II since patient compliance is much higher and symptom improvement is identical. 8 Even lighter weight compression has been studied for subjective complaints and objective signs (Doppler measured reflux) of lower extremity venous insufficiency. Over-the-calf compression socks of 6 and 12 mmHg were shown to improve venous insufficiency objectively and subjectively.…”
Section: Conclusion Use Of Lightweight (Low Compression) Rtw Gradiementioning
confidence: 99%
“…Therefore class I compression may be recommended over class II since patient compliance is much higher and symptom improvement is identical. 8 …”
mentioning
confidence: 99%